Pengaruh Marketing Mix Terhadap Keputusan Pembelian Pada CV. Justiti Motor Lembata - Barcelona, Oktavianus; Tumbel, Tinneke M.; Kalangi, Johnny A. F (Sam Ratulangi University, 2019)
Related research to study the large influence of mixed mixtures on purchasing decisions onCV. Justitia Lembata Motor can compete from several of the same companies in motorcyclesales. Partially significant for purchasing decisions. Marketing mix is a combination of fourvariables or activities which are the core of the marketing system, namely: products, pricestructures, promotional activities, and distribution systems. Consumer purchasing decisionsare the final purchases of consumers both individuals and households, who buy goods andservices for personal purchases. This research uses quantitative methods, data collectiontechniques using questionnaires. The population in this study were motorcycle buyers andcustomers at CV. Justin Motor Lembata. The sample taken was 50 respondents using simplerandom sampling technique. The research method used is simple linear regression. The 0.014constant is the same as the result of the buyer's decision to buy at 0.014% and the regressioncoefficient of the marketing mix variable is 0.667 units to one so that the purchasing decisionincreases by 0.667%.